Surface-induced phase transitions of wormlike chains in slit confinement. Issue 11 (15th February 2016) - Ye, Shiwei; Zhang, Pingwen; Chen, Jeff Z. Y.
Abstract : As the overall density increases, a semiflexible polymer fluid confined in a slit displays three orientational states, stage by stage. The main-axis orientational distributions of different states near the surface have different characteristics. Abstract : On the basis of a self-consistent field theory treatment of semi-flexible polymer chains, we analyze the effects of the flexibility on the structure of polymers sterically confined between two parallel, structureless walls separated by a distance. The model is built from a wormlike chain formalism which crosses over from the rod limit to the flexible limit, and the Onsager-type interaction which describes the orientation-dependent excluded-volume interaction. Three surface states were obtained from the numerical solution to the theory: uniaxial, biaxial, and condensed. As the overall density increases in such a lyotropic system, first order phase transitions between uniaxial and biaxial states, biaxial and condensed states can occur.